HUBUNGAN ANTARA INTENSITAS PENGGUNAAN SMARTPHONE DENGAN RISIKO KEMUNCULAN SINDROM DE QUERVAIN PADA MAHASISWI PROGRAM STUDI SARJANA KEDOKTERAN DAN PROFESI DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Elvina Veronica; I Dewa Ayu Inten Dwi Primayanti; I Putu Gede Adiatmika (E-Jurnal Medika Udayana, 2021)
ABSTRACT The intensity of smartphone usage among students is high because the presence of smartphones that support our activities. Many negative effects caused by the intensity of excessive smartphone usage such as musculoskeletal disorders. De Quervain's syndrome is a painful condition of the stiloid processus due to synovial wrapper sheath trauma or inflammation that surrounds the abductor polllicis longus muscle and extensor pollicis brevis muscle in the hand due to excessive repetitive movements. This study was an analytic study with a cross-sectional method to determine the relationship of the intensity of smartphone usage with the risk of de Quervain's syndrome appearance in undergraduate female medical students of Udayana University. Conducted in February-March 2020 at the Faculty of Medicine, Udayana University with 100 undergraduate female medical student of Udayana University class of 2018 and 2019 as respondents who filled DQST (de Quervain Screening Tool) questionnaire on both hands and a questionnaire about intensity of smartphone usage. This research variable consists of independent variable intensity of smartphone usage, dependent variable de Quervain syndrome of both hands, and control variable age, gender, and medical study program. Somers’ D bivariate test results showed no relationship (p> 0.05) between intensity of smartphone usage and risk of de Quervain appearance on both hands. This condition was influenced by position when using a smartphone, type of smartphone, and other factors. Further research is needed related to other factors that influence the risk of de Quervain syndrome appearance and other musculoskeletal disorders. Keywords: de Quervain syndrome, intensity of smartphone usage, pain